Minat Siswa Terhadap Pembelajaran Matematika di Sekolah Dasar: Tinjauan Teori Kebutuhan Maslow - Rahma, Fatikh Inayahtur (JAMBURA Elementary Education Journal, 2024)
Influences student learning interest is student motivation towards learning mathematics. Abraham H. Maslow's theory of motivation is one of the motivational theories that can be used to foster student interest in learning mathematics. Maslow's theory consists of five stages, namely physiological needs, safety needs, social needs, self-esteem needs and self-actualization needs. This research method uses descriptive qualitative by collecting data through observation and interviews at SDI KHA. Wahid Hasyim. In the first stage of Maslow's theory, is the fulfillment of physiological needs, namely the fulfillment of food and drink and the provision of infrastructure needed by students. The second stage is the need for security. This need is no more bullying or actions that can hurt students when learning mathematics. In the third stage, the interaction between the teacher and students must be well established. This has an impact on the growing interest and motivation of students in learning mathematics. In the fourth stage is giving awards to students. The fifth stage is to provide opportunities for students to actualize themselves by providing opportunities to express opinions and present their work.